Pengendalain Harga Pokok Produksi Dengan Metode Full Costing Pada “Kerupuk Sari Udang Mbah Oerip-Sidoarjo” - Darno Darno (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Companies must be able to compete in terms of prices by managing the handling of raw materials, labor and overhaed factories. All three are very important because they directly affect the cost of the product (HPP). UD company Redjo Makmoer Indonesia, is a company that produces crackers. For the determination of production costs and pricing of sales, the company makes a policy on the method of calculating the cost of production. In addition to pricing, also to control the process and reduce the size of the company's production costs. Based on observations for one month the production process, the cost of production with the method of the company that has been run is Rp. 40,100.00. With the full costing method, Rp. 41,500.00. It can be concluded that the cost of production based on the two calculation methods above there are differences or differences. With the full costing method, the cost of production is higher. This shows that so far the calculations made by the company have several elements that have not been included in the calculation.